Implementasi SAW dan AHP pada Sistem Pendukung Keputusan di Bikin Aplikasi DEV - Herawati Fransiska Dewi, Siti; Muhammad, Ali (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Bikin Aplikasi DEV is a freelance group specializing in online application and website development, often facing challenges in determining project priorities effectively. Limited resources and multiple incoming project requests make decision-making crucial. This study aims to develop a decision support system to assist the team in prioritizing projects objectively. The Analytical Hierarchy Process (AHP) method is used to assign weights to each criterion based on their level of importance, while the Simple Additive Weighting (SAW) method is applied to calculate project scores based on these weights. The implementation results show that the system can generate project rankings that align with the team’s needs and help optimize time and resource allocation. This system offers a practical and adaptive tool for freelance teams in project management, particularly when dealing with simultaneous project demands.